Production process of high-density high-capacity trimanganese tetroxide for lithium battery
Patent Information
- Application Number
- CN202611224310.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-16
AI Technical Summary
然而,常规的合成高分子模板或表面活性剂存在亲水活性位点有限、成本偏高的缺陷,难以使锰离子在模板表面实现均匀锚固和高度致密氧化,致使产物的振实密度偏低,后续碳复合时界面结合力也较弱,限制了比容量的充分发挥
[0015] The beneficial effects are: 1. This invention removes calcium and magnesium through the synergistic effect of manganese dihydrogen phosphate and zinc powder. During this process, manganese dihydrogen phosphate ions undergo a metathesis reaction with the zinc substrate on the zinc surface. Due to the release of Zn from the zinc powder... 2+ The ionic radius of Mg in manganese sulfate solution 2+Similarly, both can preferentially form isomorphous mixed-crystal phosphate precipitates with phosphate ions, thereby efficiently removing magnesium ions, while Mn... 2+ The ionic radius is relatively large, making it difficult to react with phosphate and Zn at room temperature. 2+ The formation of numerous stable lattice complex salts effectively avoids manganese co-precipitation loss, while simultaneously reducing the Ca content in the solution. 2+ It combines with dihydrogen phosphate and its hydrolyzed hydrogen phosphate ions to form insoluble calcium dihydrogen phosphate and calcium hydrogen phosphate precipitates, thus achieving thorough removal. This highly selective method for removing calcium and magnesium with extremely low manganese loss, combined with the preceding iron and heavy metal removal processes, can produce a purified manganese sulfate solution with extremely low impurity content, providing a high-quality manganese source for the subsequent synthesis of high-density, high-capacity manganese tetroxide.
Smart Images

Figure REF-OBJ-1786589451854-000001 
Figure REF-OBJ-1786589451854-000002
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery cathode material preparation technology, specifically relating to a production process for high-density, high-capacity manganese tetroxide for lithium batteries. Background Technology
[0002] Manganese tetroxide (MTO) is an indispensable key material in battery manufacturing. It appears as a black or dark brown powder composed of unique rhodochrosite-type manganese oxide whiskers. MTO has a wide and crucial application in battery manufacturing, exhibiting particularly outstanding characteristics: extremely high stability, ensuring the reliability of batteries for long-term use; high energy density, allowing it to store more energy within a limited volume, thus improving battery performance; rapid charge and discharge response, meeting the requirements of high-efficiency batteries. Even more importantly, as an environmentally friendly material, it is non-toxic and harmless, meeting the requirements of green production.
[0003] Currently, the industrial production of manganese tetroxide (MnO) primarily uses manganese sulfate solution as the manganese source, synthesized through alkaline precipitation-air oxidation or hydrothermal oxidation. The manganese sulfate solution typically originates from sulfuric acid leaching of manganese ore or manganese-containing smelting slag, and the leachate often contains significant amounts of alkaline earth metal impurities such as calcium and magnesium. To remove these impurity ions, current processes commonly employ fluorinating agents such as manganese fluoride and ammonium fluoride, causing calcium and magnesium ions to precipitate as insoluble fluorides, thus achieving separation. This method for removing calcium and magnesium has significant drawbacks: First, the fluorinating agent is expensive, which significantly increases the overall cost of raw material purification. Second, the large amount of fluorine-containing waste residue and wastewater generated during the purification process are strictly controlled hazardous wastes, which are difficult to treat harmlessly and expensive to dispose of. This can easily cause fluoride pollution in the surrounding soil and water bodies, putting enormous pressure on the ecological environment. Third, the use of fluorinating agents inevitably introduces residual fluoride ions into the manganese sulfate solution. These trace amounts of fluoride ions not only reduce the purity of the manganese sulfate solution, but also incorporate manganese tetroxide lattice or adsorb onto the product surface in subsequent oxidation reactions, weakening the electrochemical activity and structural stability of the material.
[0004] Furthermore, to enhance the electrochemical activity of manganese tetroxide and suppress its volume effect, template methods are commonly used to control the morphology of the product. However, conventional synthetic polymer templates or surfactants suffer from limitations such as limited hydrophilic active sites and high costs, making it difficult to achieve uniform anchoring and highly dense oxidation of manganese ions on the template surface. This results in low tap density of the product and weak interfacial bonding during subsequent carbon composite formation, limiting the full utilization of specific capacity. Meanwhile, in the oxidation precipitation process, industrially, a one-time addition or simple dropwise addition of alkali solution is commonly used, which easily leads to local supersaturation of the system. This causes instantaneous burst nucleation of manganese hydroxide and uncontrolled agglomeration between particles, resulting in a wide particle size distribution and loose packing of the product. This not only lowers the tap density but also makes it difficult to form a structurally stable, conductive, integrated composite material after carbonization. Summary of the Invention
[0005] To address the aforementioned technical deficiencies, this invention presents a production process for high-density, high-capacity manganese tetroxide for lithium batteries. This process is environmentally friendly and simple, and the resulting high-density, high-capacity manganese tetroxide for lithium batteries possesses both high tap density and specific capacity.
[0006] A production process for high-density, high-capacity manganese tetroxide for lithium batteries includes the following steps: S1: Preparation of purified manganese sulfate solution Manganese oxide ore powder and pyrite powder are leached in sulfuric acid at high temperature. Iron ions are removed by stepwise precise pH control using nano-calcium carbonate. Then, barium sulfide is added to precipitate and remove heavy metals, resulting in a heavy metal-free manganese sulfate solution. The pH of the heavy metal-free manganese sulfate solution is adjusted to neutral. Then, manganese dihydrogen phosphate and zinc powder are added and stirred evenly to react. The filtrate is filtered and the concentration is adjusted to obtain a purified manganese sulfate solution. S2: Preparation of microalgae-based oxygen-enriched cellulose template Formic acid and choline chloride were heated and mixed evenly to obtain a eutectic solvent. Chlorella was added to deionized water, and then the eutectic solvent was added and mixed evenly. The mixture was then transferred to a reaction vessel for hydrothermal treatment. The precipitate was collected, washed, dried and pulverized to obtain an oxygen-enriched cellulose template of Chlorella. S3: Preparation of manganese tetroxide using the oxygen-cellulose template method Add Chlorella oxygen-enriched cellulose template and pure water to the oxidation reactor. After heating to 85-90℃, introduce high-purity oxygen at a flow rate of 1-1.2 L / min. Simultaneously add ammonia and purified manganese sulfate solution to the reactor using a peristaltic pump at a rate of 8-10 mL / min for 1-1.5 h. Filter and collect the residue to obtain Chlorella cellulose loaded with manganese tetroxide. Then, remove the cellulose by shaking in a cellulose solvent to obtain high-density, high-capacity manganese tetroxide.
[0007] Furthermore, the purification and preparation of the manganese sulfate solution in step S1 specifically includes the following steps: S1.1: Manganese oxide ore powder, pyrite powder, and 98% sulfuric acid are added to a leaching reaction tank at a mass ratio of 1:(0.3-0.4):(0.4-0.6). The mixture is reacted at 90-95℃ and 250-300rpm for 3-4 hours to obtain a mixed slurry. While maintaining a constant temperature, nano-calcium carbonate powder is added to the mixed slurry to adjust the pH to 4-4.5. The content of ferrous ions in the mixed slurry is then tested. If the ferrous ion content is ≥10... -5 If the concentration is mol / L, add manganese oxide ore powder that has passed through a 325-mesh sieve until the ferrous ion content is <10 mol / L. -5 The concentration was adjusted to mol / L, and then nano-calcium carbonate powder was added to adjust the pH to 6-6.5. The content of ferric ions was then tested. If the content of ferric ions was ≥10 mol / L, the solution was considered ferrous ions. -5 If the concentration is mol / L, continue adding nano-calcium carbonate powder until the ferric ion content is <10 mol / L. -5 mol / L, filter under pressure to obtain crude manganese sulfate solution; S1.2: Heat the crude manganese sulfate solution to 80-90℃, then slowly add barium sulfide and stir for 1.5-2 hours. The solid-liquid ratio of barium sulfide to crude manganese sulfate solution is 1:(30-50)g / mL. Filter the solution to obtain a heavy metal-free manganese sulfate solution. S1.3: At 20-25℃, add a pH adjuster to adjust the pH to 7 to the heavy metal-free manganese sulfate solution, then add manganese dihydrogen phosphate and zinc powder and stir evenly. React for 30-35 minutes, filter and take the filtrate, adjust the concentration to 0.4-0.5 mol / L to obtain a purified manganese sulfate solution.
[0008] Furthermore, the preparation of the microalgae-based oxygen-rich cellulose template in step S2 specifically includes the following steps: S2.1: Mix formic acid and choline chloride in a 1:1 molar ratio in a container and stir at 75-80℃ and 150-200rpm for 1-1.5h to obtain a eutectic solvent; S2.2: Add Chlorella to deionized water to prepare a Chlorella solution with a Chlorella concentration of 120-150 g / L. Add a eutectic solvent to the Chlorella solution and mix well to obtain a pretreatment solution. S2.3: Transfer the pretreatment solution to the reactor, seal the reactor, and perform hydrothermal treatment at 100-120℃ for 10-15 min. Then filter the product in the reactor, collect the precipitate, wash it with deionized water 3-4 times, dry it in an oven at 60-65℃ for 8-10 h, and pulverize it through a 20-30 mesh sieve to obtain the Chlorella oxygen-enriched cellulose template.
[0009] Furthermore, step S3, the preparation of manganese tetroxide using the oxygen-cellulose template method, specifically includes the following steps: S3.1: Add 8-10 parts of Chlorella oxygen-enriched cellulose template and 100-120 parts of pure water to the oxidation reactor. After heating to 85-90℃, introduce high-purity oxygen into the reactor. Set the oxygen flow rate to 1-1.2L / min. Simultaneously add ammonia water and purified manganese sulfate solution to the reactor using a peristaltic pump. The dropping rate of both ammonia water and purified manganese sulfate solution is 8-10mL / min. The total amount added is based on manganese sulfate, which accounts for 30-35% of the mass of the Chlorella oxygen-enriched cellulose template. After the dropping is completed, keep the temperature for 1-1.5h. Filter and collect the filter residue. Rinse the surface of the filter residue with deionized water to remove the residual solution and then dry it to obtain Chlorella cellulose loaded with manganese tetroxide. S3.2: Mix triethylammonium hydroxide and N,N,N-trimethyl-1-adamantyl ammonium hydroxide at a mass ratio of 1:(18-20) in a container, then add deionized water to prepare a cellulose solvent. The molar concentration of N,N,N-trimethyl-1-adamantyl ammonium hydroxide in the cellulose solvent is 1-1.5 mol / L. Place the cellulose of Chlorella loaded with manganese tetroxide in the cellulose solvent at a solid-liquid ratio of 1:(12-15) g / mL and shake for 8-10 min. Filter and collect the residue. Rinse with deionized water 3-4 times, then dry in an oven at 80-100℃ to constant weight to obtain high-density, high-capacity manganese tetroxide.
[0010] Furthermore, the pH adjuster in step S1.3 is manganese carbonate.
[0011] Further, in step S1.3, the mass ratio of manganese dihydrogen phosphate, the mass of zinc powder, and the volume ratio of manganese sulfate solution (excluding heavy metals) is 1 g : (3-5) g : (25-30) mL.
[0012] Furthermore, in step S2.2, the volume ratio of the eutectic solvent to the Chlorella solution is 1:(3-4).
[0013] Furthermore, the molar concentration of ammonia in step S3.1 is 1.2-1.5 mol / L.
[0014] A high-density, high-capacity manganese tetroxide for lithium batteries is prepared by the aforementioned production process of high-density, high-capacity manganese tetroxide for lithium batteries.
[0015] The beneficial effects are: 1. This invention removes calcium and magnesium through the synergistic effect of manganese dihydrogen phosphate and zinc powder. During this process, manganese dihydrogen phosphate ions undergo a metathesis reaction with the zinc substrate on the zinc surface. Due to the release of Zn from the zinc powder... 2+ The ionic radius of Mg in manganese sulfate solution 2+Similarly, both can preferentially form isomorphous mixed-crystal phosphate precipitates with phosphate ions, thereby efficiently removing magnesium ions, while Mn... 2+ The ionic radius is relatively large, making it difficult to react with phosphate and Zn at room temperature. 2+ The formation of numerous stable lattice complex salts effectively avoids manganese co-precipitation loss, while simultaneously reducing the Ca content in the solution. 2+ It combines with dihydrogen phosphate and its hydrolyzed hydrogen phosphate ions to form insoluble calcium dihydrogen phosphate and calcium hydrogen phosphate precipitates, thus achieving thorough removal. This highly selective method for removing calcium and magnesium with extremely low manganese loss, combined with the preceding iron and heavy metal removal processes, can produce a purified manganese sulfate solution with extremely low impurity content, providing a high-quality manganese source for the subsequent synthesis of high-density, high-capacity manganese tetroxide.
[0016] 2. In this invention, Chlorella is pretreated with a eutectic solvent followed by hydrothermal reaction to obtain a cellulose template rich in hydroxyl groups and various oxygen-containing functional groups on its surface. The abundant hydroxyl groups can serve as highly active anchoring sites, uniformly adsorbing Mn through hydrogen bonding or coordination. 2+ This induces in-situ nucleation and oriented formation of manganese tetroxide along the surface of the cellulose template, effectively preventing particle aggregation. Furthermore, the oxygen-rich and porous nature of the cellulose template promotes oxygen transfer and electron transfer in subsequent oxidation reactions, allowing Mn to... 2+ The oxidation and crystallization are more complete, thus giving manganese tetroxide a high packing density and a large specific surface area.
[0017] 3. This invention involves the co-current dropwise addition of ammonia and purified manganese sulfate solution to a reaction system containing an oxygen-enriched cellulose template from Chlorella, while continuously introducing precisely controlled high-purity oxygen at a suitable temperature. The reaction is then carried out by shaking in a cellulose solvent to remove the cellulose, yielding high-density, high-capacity manganese tetroxide. The co-current dropwise addition process, combined with specific parameters (oxygen flow rate 1-1.2 L / min, dropping rate 8-10 mL / min, temperature 85-90℃), facilitates the release of ammonia and the production of manganese tetroxide. 2+ The supply and the rate of oxidation crystallization are highly coordinated, avoiding disordered nucleation caused by a sudden increase in local supersaturation. The entire oxidation precipitation process proceeds smoothly on the surface of the cellulose template, generating a layer of manganese tetroxide particles with high crystallinity, uniform particle size and dense packing, giving manganese tetroxide high density and large specific surface area. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Unless otherwise specified, all parts mentioned in the following examples refer to parts by weight.
[0020] Example 1
[0021] A production process for high-density, high-capacity manganese tetroxide for lithium batteries specifically includes the following steps: S1: Preparation of purified manganese sulfate solution S1.1: Manganese oxide ore powder, pyrite powder, and 98% sulfuric acid were added to a leaching reaction tank at a mass ratio of 1:0.3:0.4 and reacted at 90℃ and 250rpm for 3 hours to obtain a mixed slurry. While maintaining a constant temperature, nano-calcium carbonate powder was added to the mixed slurry to adjust the pH to 4. The content of ferrous ions in the mixed slurry was then measured. If the ferrous ion content was ≥10... -5 If the concentration is mol / L, add manganese oxide ore powder that has passed through a 325-mesh sieve until the ferrous ion content is <10 mol / L. -5 The concentration was increased to mol / L, and then nano-calcium carbonate powder was added to adjust the pH to 6. The content of ferric ions was then measured. If the content of ferric ions was ≥10 mol / L, the result was positive. -5 If the concentration is mol / L, continue adding nano-calcium carbonate powder until the ferric ion content is <10 mol / L. -5 mol / L, filter under pressure to obtain crude manganese sulfate solution; S1.2: Heat the crude manganese sulfate solution to 80℃, then slowly add barium sulfide and stir for 1.5h. The solid-liquid ratio of barium sulfide to crude manganese sulfate solution is 1:30g / mL. Filter the solution by pressure to obtain a heavy metal-free manganese sulfate solution. S1.3: At 20℃, add manganese carbonate to the heavy metal-removing manganese sulfate solution to adjust the pH to 7, then add manganese dihydrogen phosphate and zinc powder and stir evenly. The mass ratio of manganese dihydrogen phosphate, zinc powder and heavy metal-removing manganese sulfate solution is 1g:3g:25mL. React for 30min, filter and take the filtrate, adjust the concentration to 0.4mol / L to obtain purified manganese sulfate solution.
[0022] S2: Preparation of microalgae-based oxygen-enriched cellulose template S2.1: Formic acid and choline chloride are mixed in a 1:1 molar ratio and placed in a container. The mixture is stirred at 75°C and 150 rpm for 1 hour to obtain a eutectic solvent. S2.2: Chlorella was added to deionized water to prepare a Chlorella solution with a concentration of 120 g / L. A eutectic solvent was added to the Chlorella solution and mixed evenly. The volume ratio of the eutectic solvent to the Chlorella solution was 1:3 to obtain the pretreatment solution. The Chlorella was purchased from a commercial biotechnology company. S2.3: Transfer the pretreatment solution to the reactor, seal the reactor, and perform hydrothermal treatment at 100℃ for 10 min. Then filter the product in the reactor, collect the precipitate and wash it three times with deionized water. Dry it in an oven at 60℃ for 8 h, pulverize it through a 20-mesh sieve, and obtain the Chlorella oxygen-enriched cellulose template.
[0023] S3: Preparation of manganese tetroxide using the oxygen-cellulose template method S3.1: Add 8 parts of Chlorella oxygen-enriched cellulose template and 100 parts of pure water to the oxidation reactor. After heating to 85℃, introduce high-purity oxygen into the reactor. Set the oxygen flow rate to 1L / min. Simultaneously add ammonia water with a molar concentration of 1.2mol / L and purified manganese sulfate solution to the reactor using a peristaltic pump. The dropping rate of ammonia water and purified manganese sulfate solution is 8mL / min. The total amount added is calculated based on manganese sulfate, which accounts for 30% of the mass of Chlorella oxygen-enriched cellulose template. After the dropping is completed, keep warm for 1h. Filter and collect the filter residue. Rinse the surface of the filter residue with deionized water to remove the residual solution and then dry it to obtain Chlorella cellulose loaded with manganese tetroxide. S3.2: Triethylammonium hydroxide and N,N,N-trimethyl-1-adamantylammonium hydroxide were mixed in a mass ratio of 1:18 in a container, and then deionized water was added to prepare a cellulose solvent. The molar concentration of N,N,N-trimethyl-1-adamantylammonium hydroxide in the cellulose solvent was 1 mol / L. Chlorella tetroxide-loaded cellulose was placed in the cellulose solvent at a solid-liquid ratio of 1:12 g / mL and shaken for 8 min. The residue was collected by filtration, rinsed 3 times with deionized water, and then dried in an oven at 80℃ to constant weight to obtain high-density, high-capacity manganese tetroxide.
[0024] Example 2
[0025] A production process for high-density, high-capacity manganese tetroxide for lithium batteries specifically includes the following steps: S1: Preparation of purified manganese sulfate solution S1.1: Manganese oxide ore powder, pyrite powder, and 98% sulfuric acid were added to a leaching reaction tank at a mass ratio of 1:0.35:0.5 and reacted at 90℃ and 275 rpm for 4 hours to obtain a mixed slurry. While maintaining a constant temperature, nano-calcium carbonate powder was added to the mixed slurry to adjust the pH to 4. The content of ferrous ions in the mixed slurry was then measured. If the ferrous ion content was ≥10... -5 If the concentration is mol / L, add manganese oxide ore powder that has passed through a 325-mesh sieve until the ferrous ion content is <10 mol / L. -5 The concentration was adjusted to mol / L, and then nano-calcium carbonate powder was added to adjust the pH to 6.5. The content of ferric ions was then measured. If the content of ferric ions was ≥10 mol / L, the result was considered positive. -5 If the concentration is mol / L, continue adding nano-calcium carbonate powder until the ferric ion content is <10 mol / L.-5 mol / L, filter under pressure to obtain crude manganese sulfate solution; S1.2: Heat the crude manganese sulfate solution to 85℃, then slowly add barium sulfide and stir for 1.5h. The solid-liquid ratio of barium sulfide to crude manganese sulfate solution is 1:40g / mL. Filter the solution by pressure to obtain a heavy metal-free manganese sulfate solution. S1.3: At 25℃, add manganese carbonate to the heavy metal-removing manganese sulfate solution to adjust the pH to 7, then add manganese dihydrogen phosphate and zinc powder and stir evenly. The mass ratio of manganese dihydrogen phosphate, zinc powder and heavy metal-removing manganese sulfate solution is 1g:4g:28mL. React for 30min, filter and take the filtrate, adjust the concentration to 0.45mol / L to obtain purified manganese sulfate solution.
[0026] S2: Preparation of microalgae-based oxygen-enriched cellulose template S2.1: Formic acid and choline chloride are mixed in a 1:1 molar ratio and placed in a container. The mixture is stirred at 77°C and 175 rpm for 1.5 h to obtain a eutectic solvent. S2.2: Chlorella was added to deionized water to prepare a Chlorella solution with a concentration of 135 g / L. A eutectic solvent was added to the Chlorella solution and mixed evenly. The volume ratio of the eutectic solvent to the Chlorella solution was 1:3.5 to obtain the pretreatment solution. The Chlorella was purchased from a commercial biotechnology company. S2.3: Transfer the pretreatment solution to the reactor, seal the reactor, and perform hydrothermal treatment at 110℃ for 12 min. Then filter the product in the reactor, collect the precipitate and wash it 4 times with deionized water. Dry it in an oven at 65℃ for 8 h, and then pulverize it through a 20-mesh sieve to obtain the Chlorella oxygen-enriched cellulose template.
[0027] S3: Preparation of manganese tetroxide using the oxygen-cellulose template method S3.1: Add 9 parts of Chlorella oxygen-enriched cellulose template and 110 parts of pure water to the oxidation reactor. After heating to 90℃, introduce high-purity oxygen into the reactor. The oxygen flow rate is set to 1.1L / min. Simultaneously add ammonia water with a molar concentration of 1.3mol / L and purified manganese sulfate solution to the reactor using a peristaltic pump. The dropping rate of ammonia water and purified manganese sulfate solution is 9mL / min. The total amount added is calculated as manganese sulfate, which accounts for 30-35% of the mass of Chlorella oxygen-enriched cellulose template. After the dropping is completed, keep warm for 1.2h. Filter and collect the filter residue. Rinse the surface of the filter residue with deionized water to remove the residual solution and then dry it to obtain Chlorella cellulose loaded with manganese tetroxide. S3.2: Triethylammonium hydroxide and N,N,N-trimethyl-1-adamantylammonium hydroxide were mixed in a container at a mass ratio of 1:19, and then deionized water was added to prepare a cellulose solvent. The molar concentration of N,N,N-trimethyl-1-adamantylammonium hydroxide in the cellulose solvent was 1.2 mol / L. Chlorella tetroxide-loaded cellulose was placed in the cellulose solvent at a solid-liquid ratio of 1:14 g / mL and shaken for 9 min. The residue was collected by filtration, rinsed 4 times with deionized water, and then dried in a 90℃ oven to constant weight to obtain high-density, high-capacity manganese tetroxide.
[0028] Example 3
[0029] A production process for high-density, high-capacity manganese tetroxide for lithium batteries specifically includes the following steps: S1: Preparation of purified manganese sulfate solution S1.1: Manganese oxide ore powder, pyrite powder, and 98% sulfuric acid were added to a leaching reaction tank at a mass ratio of 1:0.4:0.6 and reacted at 95℃ and 300rpm for 4 hours to obtain a mixed slurry. While maintaining a constant temperature, nano-calcium carbonate powder was added to the mixed slurry to adjust the pH to 4.5. The content of ferrous ions in the mixed slurry was then measured. If the ferrous ion content was ≥10... -5 If the concentration is mol / L, add manganese oxide ore powder that has passed through a 325-mesh sieve until the ferrous ion content is <10 mol / L. -5 The concentration was adjusted to mol / L, and then nano-calcium carbonate powder was added to adjust the pH to 6.5. The content of ferric ions was then measured. If the content of ferric ions was ≥10 mol / L, the result was considered positive. -5 If the concentration is mol / L, continue adding nano-calcium carbonate powder until the ferric ion content is <10 mol / L. -5 mol / L, filter under pressure to obtain crude manganese sulfate solution; S1.2: Heat the crude manganese sulfate solution to 90℃, then slowly add barium sulfide and stir for 2 hours. The solid-liquid ratio of barium sulfide to crude manganese sulfate solution is 1:50 g / mL. Filter the solution by pressure to obtain a heavy metal-free manganese sulfate solution. S1.3: At 25℃, add manganese carbonate to the heavy metal-free manganese sulfate solution to adjust the pH to 7, then add manganese dihydrogen phosphate and zinc powder and stir evenly. The mass ratio of manganese dihydrogen phosphate, zinc powder and heavy metal-free manganese sulfate solution is 1g:5g:30mL. React for 35min, filter and take the filtrate, adjust the concentration to 0.5mol / L to obtain purified manganese sulfate solution.
[0030] S2: Preparation of microalgae-based oxygen-enriched cellulose template S2.1: Formic acid and choline chloride are mixed in a 1:1 molar ratio and placed in a container. The mixture is stirred at 80°C and 200 rpm for 1.5 h to obtain a eutectic solvent. S2.2: Chlorella was added to deionized water to prepare a Chlorella solution with a concentration of 150 g / L. A eutectic solvent was added to the Chlorella solution and mixed evenly. The volume ratio of the eutectic solvent to the Chlorella solution was 1:4 to obtain the pretreatment solution. The Chlorella was purchased from a commercial biotechnology company. S2.3: Transfer the pretreatment solution to the reactor, seal the reactor, and perform hydrothermal treatment at 120℃ for 15 min. Then filter the product in the reactor, collect the precipitate and wash it 4 times with deionized water. Dry it in an oven at 65℃ for 10 h, pulverize it through a 30-mesh sieve, and obtain the Chlorella oxygen-enriched cellulose template.
[0031] S3: Preparation of manganese tetroxide using the oxygen-cellulose template method S3.1: Add 10 parts of Chlorella oxygen-enriched cellulose template and 120 parts of pure water to the oxidation reactor. After heating to 90℃, introduce high-purity oxygen into the reactor. Set the oxygen flow rate to 1.2L / min. Simultaneously add ammonia water with a molar concentration of 1.5mol / L and purified manganese sulfate solution to the reactor using a peristaltic pump. The addition rate of both ammonia water and purified manganese sulfate solution is 10mL / min. The total amount added is calculated based on manganese sulfate, which accounts for 30-35% of the mass of Chlorella oxygen-enriched cellulose template. After the addition is completed, keep the temperature for 1.5h. Filter and collect the filter residue. Rinse the surface of the filter residue with deionized water to remove the residual solution and then dry it to obtain Chlorella cellulose loaded with manganese tetroxide. S3.2: Triethylammonium hydroxide and N,N,N-trimethyl-1-adamantylammonium hydroxide were mixed in a container at a mass ratio of 1:20. Then, deionized water was added to prepare a cellulose solvent. The molar concentration of N,N,N-trimethyl-1-adamantylammonium hydroxide in the cellulose solvent was 1.5 mol / L. Chlorella tetroxide-loaded cellulose was placed in the cellulose solvent at a solid-liquid ratio of 1:15 g / mL and shaken for 10 min. The residue was collected by filtration, rinsed 4 times with deionized water, and then dried in an oven at 100℃ to constant weight to obtain high-density, high-capacity manganese tetroxide.
[0032] Comparative Example 1: The difference from Example 1 is that the heavy metal-removing manganese sulfate solution prepared in step S1.2 is used to remove calcium and magnesium by manganese fluoride. The heavy metal-removing manganese sulfate solution is slowly added to manganese fluoride under the conditions of 85°C and pH 6, and stirred for 2-3 hours. The material-liquid ratio of manganese fluoride to heavy metal-removing manganese sulfate solution is 50:1 g / L to obtain purified manganese sulfate solution. The rest of the process is the same as in Example 1.
[0033] Comparative Example 2: The difference from Example 1 is that step S2 was removed in this comparative example, and the Chlorella oxygen-enriched cellulose template in step S3.1 was replaced with an equal mass of sugarcane bagasse cellulose. The preparation method of sugarcane bagasse cellulose is as follows: After crushing the sugarcane bagasse, it was passed through a 20-mesh sieve, washed with ethanol and water, and then dried to obtain sugarcane bagasse powder. 100 parts of a 4% NaOH aqueous solution were taken, and 0.8% hydrogen peroxide was added according to the mass of the NaOH aqueous solution. Then, 2 parts of sugarcane bagasse powder were added, and the mixture was stirred and reacted at 80°C for 4 hours. The filter residue was collected by suction filtration, washed with water until the washing liquid was neutral, and then dried to obtain sugarcane bagasse cellulose. The rest of the process was the same as in Example 1.
[0034] Comparative Example 3: The difference from Example 1 is that the oxygen flow rate in step S3.1 of this comparative example is set to 0.9 L / min, while the rest of the process is the same as in Example 1.
[0035] Comparative Example 4: The difference from Example 1 is that the oxygen flow rate in step S3.1 of this comparative example is set to 1.3 L / min, while the rest of the process is the same as in Example 1.
[0036] Comparative Example 5: The difference from Example 1 is that the dropping rate of ammonia and purified manganese sulfate solution in step S3.1 of this comparative example is set to 7 mL / min, while the rest of the process is the same as in Example 1.
[0037] Comparative Example 6: The difference from Example 1 is that the dropping rate of ammonia and purified manganese sulfate solution in step S3.1 of this comparative example is set to 11 mL / min, while the rest of the process is the same as in Example 1.
[0038] The manganese tetroxide prepared in Examples 1-3 and Comparative Example 1 was used as samples. The manganese content in the samples was determined by ferrous ammonium sulfate titration. Three samples from different batches were measured, and the average value was recorded. The test results are shown in Table 1.
[0039] Table 1: Manganese content of manganese tetroxide
[0040] As shown in Table 1, the manganese content of the manganese tetroxide prepared in Examples 1-3 was 71.91%-71.96%, while the manganese content of the product obtained by removing calcium and magnesium using manganese fluoride in Comparative Example 1 was only 70.85%. This directly proves that the present invention, under normal temperature and neutral conditions, utilizes manganese dihydrogen phosphate and zinc powder to synergistically remove calcium and magnesium, selectively precipitating calcium and magnesium ions and effectively avoiding the co-precipitation loss of manganese, producing a purified manganese sulfate solution with extremely low impurities, thus ensuring the ultra-high purity of the final product, manganese tetroxide; while the traditional fluorination method introduces fluoride ions and other impurities, resulting in a significant decrease in product purity.
[0041] Tap density and specific surface area are key to achieving high energy storage in electrode materials. High tap density and large specific surface area result in high energy storage of the cathode material and high battery capacity.
[0042] Tap density test: The manganese tetroxide prepared in Examples 1-3 and Comparative Examples 1-6 were used as samples. 20g of each sample was placed in a stainless steel graduated cylinder and vibrated for 10min in a JZ-1 powder tap density tester. The amplitude height was 50mm and the vibration frequency was 60 times / min. The volume v of the sample powder was read and the tap density was 20 / v. Each group of samples was tested three times and the average value was recorded as shown in Table 2.
[0043] Specific surface area test: The specific surface area of manganese tetroxide samples prepared in Examples 1-3 and Comparative Examples 1-6 was analyzed using a specific surface area and pore size analyzer. The adsorbed gas used in the experiment was N2, the degassing temperature was 300℃, and the degassing time was 6h. Each group of samples was tested and analyzed three times, and the average value was recorded as shown in Table 2.
[0044] Table 2: Tap density and specific surface area of manganese tetroxide
[0045] As shown in Table 2, the tap density of Examples 1-3 reached 2.93-2.98 g / cm³. 3 Its specific surface area reaches 1.105-1.117 m². 2 / g; In Comparative Example 2, after replacing the microalgae-based template with sugarcane bagasse cellulose, the tap density dropped sharply to 2.03 g / cm³. 3 The specific surface area decreased to 0.72 m². 2 / g, the decrease was extremely significant. This fully demonstrates that the microalgae-based oxygen-rich cellulose template prepared by eutectic solvent-hydrothermal treatment, with its abundant hydroxyl and oxygen-containing functional groups, can efficiently anchor Mn. 2+ It induces the dense in-situ growth of manganese tetroxide along the template and effectively inhibits aggregation. Its oxygen-rich interface also promotes the oxidation reaction, thereby giving the product high bulk density and large specific surface area. In contrast, ordinary sugarcane bagasse cellulose has insufficient active sites and no oxygen-rich characteristics, and cannot achieve similar template regulation advantages.
[0046] As shown in Table 2, a comparison between Example 1 and Comparative Examples 3-6 reveals that when the oxygen flow rate decreases to 0.9 L / min (Comparative Example 3) or increases to 1.3 L / min (Comparative Example 4), and the dropping rates of ammonia and manganese sulfate decrease to 7 mL / min (Comparative Example 5) or increase to 11 mL / min (Comparative Example 6), the tap density and specific surface area of the products both show significant decreases. This indicates that only under synergistic parameters such as an oxygen flow rate of 1-1.2 L / min and a dropping rate of 8-10 mL / min can the release of ammonia and manganese sulfate be effectively controlled. 2+Only by precisely matching the supply and oxidation rates of oxygen can the reaction proceed smoothly and directionally, generating a highly crystalline, uniformly sized, and densely packed manganese tetroxide layer, thereby simultaneously achieving high tap density and high specific surface area; any deviation of any parameter will trigger local supersaturation bursts or insufficient oxidation, destroying the density and uniformity of the product.
[0047] In summary, the comparative experiments of Examples 1-3 and Comparative Examples 1-6 strongly demonstrate that the present invention successfully prepared manganese tetroxide material with ultra-high purity, high tap density, and high specific surface area through fluorine-free calcium and magnesium removal purification technology, directional induction growth of microalgae-based oxygen-rich cellulose template, and precise synergistic control of co-current oxidation deposition process parameters. This lays the foundation for its use as a cathode material in lithium batteries to achieve high capacity and high energy density.
[0048] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A production process for high-density, high-capacity manganese tetroxide for lithium batteries, characterized in that, Includes the following steps: S1: Preparation of purified manganese sulfate solution; Manganese oxide ore powder and pyrite powder are leached in sulfuric acid at high temperature. Iron ions are removed by stepwise precise pH control using nano-calcium carbonate. Then, barium sulfide is added to precipitate and remove heavy metals, resulting in a heavy metal-free manganese sulfate solution. The pH of the heavy metal-free manganese sulfate solution is adjusted to neutral. Then, manganese dihydrogen phosphate and zinc powder are added and stirred evenly to react. The filtrate is filtered and the concentration is adjusted to obtain a purified manganese sulfate solution. S2: Preparation of microalgae-based oxygen-rich cellulose template; Formic acid and choline chloride were mixed and heated until homogeneous to obtain a eutectic solvent. Chlorella was added to deionized water, and then the eutectic solvent was added and mixed until homogeneous. The mixture was then transferred to a reaction vessel for hydrothermal treatment. The precipitate was collected, washed, dried and pulverized to obtain an oxygen-enriched cellulose template of Chlorella. S3: Manganese tetroxide was prepared by the oxygen-cellulose template method; Add Chlorella oxygen-enriched cellulose template and pure water to the oxidation reactor. After heating to 85-90℃, introduce high-purity oxygen at a flow rate of 1-1.2 L / min. Simultaneously add ammonia and purified manganese sulfate solution to the reactor using a peristaltic pump at a rate of 8-10 mL / min for 1-1.5 h. Filter and collect the residue to obtain Chlorella cellulose loaded with manganese tetroxide. Then, remove the cellulose by shaking in a cellulose solvent to obtain high-density, high-capacity manganese tetroxide.
2. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 1, characterized in that, Step S1, the purification and preparation of manganese sulfate solution, specifically includes the following steps: S1.1: Manganese oxide ore powder, pyrite powder, and 98% sulfuric acid are added to a leaching reaction tank at a mass ratio of 1:(0.3-0.4):(0.4-0.6). The mixture is reacted at 90-95℃ and 250-300rpm for 3-4 hours to obtain a mixed slurry. While maintaining a constant temperature, nano-calcium carbonate powder is added to the mixed slurry to adjust the pH to 4-4.
5. The content of ferrous ions in the mixed slurry is then tested. If the ferrous ion content is ≥10... -5 If the concentration is mol / L, add manganese oxide ore powder that has passed through a 325-mesh sieve until the ferrous ion content is <10 mol / L. -5 The concentration was adjusted to mol / L, and then nano-calcium carbonate powder was added to adjust the pH to 6-6.
5. The content of ferric ions was then tested. If the content of ferric ions was ≥10 mol / L, the solution was considered ferrous ions. -5 If the concentration is mol / L, continue adding nano-calcium carbonate powder until the ferric ion content is <10 mol / L. -5 mol / L, filter under pressure to obtain crude manganese sulfate solution; S1.2: Heat the crude manganese sulfate solution to 80-90℃, then slowly add barium sulfide and stir for 1.5-2 hours. The solid-liquid ratio of barium sulfide to crude manganese sulfate solution is 1:(30-50)g / mL. Filter the solution to obtain a heavy metal-free manganese sulfate solution. S1.3: At 20-25℃, add a pH adjuster to adjust the pH to 7 to the heavy metal-free manganese sulfate solution, then add manganese dihydrogen phosphate and zinc powder and stir evenly. React for 30-35 minutes, filter and take the filtrate, adjust the concentration to 0.4-0.5 mol / L to obtain a purified manganese sulfate solution.
3. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 2, characterized in that, Step S2, the preparation of the microalgae-based oxygen-enriched cellulose template, specifically includes the following steps: S2.1: Mix formic acid and choline chloride in a 1:1 molar ratio in a container and stir at 75-80℃ and 150-200rpm for 1-1.5h to obtain a eutectic solvent; S2.2: Add Chlorella to deionized water to prepare a Chlorella solution with a Chlorella concentration of 120-150 g / L. Add a eutectic solvent to the Chlorella solution and mix well to obtain a pretreatment solution. S2.3: Transfer the pretreatment solution to the reactor, seal the reactor, and perform hydrothermal treatment at 100-120℃ for 10-15 min. Then filter the product in the reactor, collect the precipitate, wash it with deionized water 3-4 times, dry it in an oven at 60-65℃ for 8-10 h, and pulverize it through a 20-30 mesh sieve to obtain the Chlorella oxygen-enriched cellulose template.
4. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 3, characterized in that, Step S3, the preparation of manganese tetroxide using the oxygen-cellulose template method, specifically includes the following steps: S3.1: Add 8-10 parts of Chlorella oxygen-enriched cellulose template and 100-120 parts of pure water to the oxidation reactor. After heating to 85-90℃, introduce high-purity oxygen into the reactor. Set the oxygen flow rate to 1-1.2L / min. Simultaneously add ammonia water and purified manganese sulfate solution to the reactor using a peristaltic pump. The dropping rate of both ammonia water and purified manganese sulfate solution is 8-10mL / min. The total amount added is based on manganese sulfate, which accounts for 30-35% of the mass of the Chlorella oxygen-enriched cellulose template. After the dropping is completed, keep the temperature for 1-1.5h. Filter and collect the filter residue. Rinse the surface of the filter residue with deionized water to remove the residual solution and then dry it to obtain Chlorella cellulose loaded with manganese tetroxide. S3.2: Mix triethylammonium hydroxide and N,N,N-trimethyl-1-adamantyl ammonium hydroxide at a mass ratio of 1:(18-20) in a container, then add deionized water to prepare a cellulose solvent. The molar concentration of N,N,N-trimethyl-1-adamantyl ammonium hydroxide in the cellulose solvent is 1-1.5 mol / L. Place the cellulose of Chlorella loaded with manganese tetroxide in the cellulose solvent at a solid-liquid ratio of 1:(12-15) g / mL and shake for 8-10 min. Filter and collect the residue. Rinse with deionized water 3-4 times, then dry in an oven at 80-100℃ to constant weight to obtain high-density, high-capacity manganese tetroxide.
5. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 2, characterized in that, The pH adjuster in step S1.3 is manganese carbonate.
6. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 2, characterized in that, In step S1.3, the mass ratio of manganese dihydrogen phosphate, zinc powder, and manganese sulfate solution (excluding heavy metals) is 1g:(3-5)g:(25-30)mL.
7. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 4, characterized in that, In step S2.2, the volume ratio of the eutectic solvent to the Chlorella solution is 1:(3-4).
8. The production process of high-density, high-capacity manganese tetroxide for lithium batteries according to claim 4, characterized in that, In step S3.1, the molar concentration of ammonia is 1.2-1.5 mol / L.
9. A high-density, high-capacity manganese tetroxide for lithium batteries, characterized in that, It is prepared by the production process of high-density, high-capacity manganese tetroxide for lithium batteries according to any one of claims 1-8.